Parallel bars. (Economist, 2011)
The article focuses on the development of parallel programming. It states that current multi-core computers are not significantly faster due to current computer software being designed to function on single-core chips. It mentions that the U.S. Defense Advanced Research Projects Agency is encouraging the development of programming tools and parallel languages that are easier for programmers to work with. It talks about the use of obscure programming languages in online social networking sites.